Family Emotional Suport With Elderly Compliance In Hypertension Management - Linawati Togatorop (International Journal of Health and Medicine, 2024)
Hypertension, often called the "silent killer," is a leading non-communicable disease contributing to high mortality and morbidity, particularly in the elderly. As individuals age, peripheral blood vessel elasticity decreases, increasing vascular resistance and leading to systolic hypertension, commonly seen in older adults. Hypertension requires long-term treatment, which can result in non-compliance among elderly patients. Family support plays a crucial role in assisting and encouraging adherence to treatment regimens. This quantitative correlation study, with a cross-sectional approach, aimed to examine the relationship between emotional family support and treatment compliance in elderly hypertensive patients. The study was conducted at the Sei Agul Health Center, with a sample size of 65 elderly individuals selected using the Slovin formula and purposive sampling technique in October 2023. The Morisky Medication Adherence Scale (MMAS-8) was used to measure treatment compliance, while the emotional support instrument was developed by the researcher. Data were analyzed using the chi-square test, showing a significant relationship between emotional family support and treatment compliance (p-value < 0.05). The findings conclude that emotional support from family positively influences the compliance of elderly patients undergoing hypertension treatment at the Sei Agul Health Center. Health workers are encouraged to involve families in supporting hypertensive patients to enhance treatment outcomes.